Solid Lipid Nanoparticles in Medicine: Formulation, Characterization and Future prospects - Sumaiya Hasim Inamdar; Shravni Sunil Kothawale; Rutuja Ramachandra Mane; Pramod Mahodey Kale; Shrivardhan Mahesh Bolaj (International Journal of Membranes, 2025)
An alternative to conventional colloidal carriers such liposomes, polymeric nanoparticles, and emulsions, solid lipid nanoparticles (SLNs) were created in the early 1990s. Benefits include targeted medicine distribution, controlled drug release, and improved stability. An extensive review of the excipients utilized, the production techniques, including the membrane contractor approach, and the possible advantages and disadvantages of SLNs is given in this work. It investigates secondary stabilization techniques like freeze-drying and spray-drying, as well as elements of SLN stability and the function of various excipients in preserving stability. There is a detailed analysis of the difficulties in producing SLN and the instrumental methods used. Particular attention is paid to drug incorporation models in SLNs, their release processes, and the analytical techniques employed to assess them. Targeted medication delivery is one of the main uses of SLNs that are highlighted in the research. The different solid lipid-based nanocarrier types—solid lipid nanoparticles, nanostructured lipid carriers, and lipid drug conjugates—as well as their structural variants are investigated. Large-scale synthesis of solid lipid nanoparticles is described using a variety of production methods. For the purpose of characterizing solid lipid nanoparticles, photon correlation spectroscopy, scanning electron microscopy, and differential scanning calorimetry are suggested as appropriate analytical techniques. The biodistribution and mode of delivery of solid lipid nanoparticles are also discussed. Solid lipid nanoparticles could transform complicated medical conditions.
Keywords: Homogenizer; Hydrophilic; Nanoparticle; bioavailability; solid lipid nanoparticles